Eksplorasi dan Karakterisasi Rizobakteri untuk Mengendalikan Jamur Fusarium fujikuroi secara In vitro - Rahma, Zola Puti; Rahma, Haliatur; Sulyanti, Eri (Universitas Andalas, 2024)
Rhizobacteria is bacteria that found in the root zone of plants. Rhizobacteria can act as biocontrol agents against Fusarium fujikuroi, the fungus that causes bakanae disease in rice plants. This study aimed to obtain rhizobacteria isolates from the roots of rice plants and to determine their characteristics as biocontrol agents against F. fujikuroi in vitro. This research consisted of two stages: 1) Exploration of rhizobacteria from the roots of rice plants in Padang City, West Sumatera, Indonesia and 2) Antagonistic character of Rhizobacteria against F. fujikuroi in vitro including: antagonistic test, hydrolytic enzyme production test (protease, amylase, and chitinase), and HCN compound production test. Based on the research, 32 rhizobacterial isolates were obtained as candidates for biological agents. All rhizobacterial isolates can suppress the growth of Fusarium fujikuroi in vitro with an inhibition percentage of 19.43-73.53%. The 4 best isolates in suppressing the growth of Fusarium fujikuroi are Kr 2.2 from Kuranji, KG 2.2 from Korong Gadang, PA 2.1 and PA 1.2 from Pasar Ambacang with an inhibition percentage of 60.39-73.53%. The four isolates are also able to produce hydrolysis enzymes (protease, amylase and chitinase) and HCN compounds